ENLISTED ORGANIZED LABOR IN OPPOSITION TO THE PROPOSED 'NO SMOKING' LEGISLATION (Tufts Archival Research Center, 2007)
Griffin Media Group List of enlisted organized labor in opposition to the proposed no smoking legislation.